Some historical insights on optical interferometry. Issue 69 (10th September 2015) - Léna, P.
Abstract : Optical interferometry for astronomy was conceived as early as 1868, succeeded in measuring a stellar diameter in 1920 and was only reborn in 1974. Soon after, several remarkable prototype instruments were built, demonstrating the potential power of this technique for stellar studies at visible and near infrared wavelengths. Meanwhile, the physics of the Earth atmosphere, which seriously impacts image quality on ground-based observatories, progressed with the emergence of adaptive optics systems. Then, during the years 1990–2005, ambitious interferometric observatories entered into service, in Europe (VLTI) and in United States (Keck, NPOI, LBT). Today, their results and promises deeply impact stellar studies by providing images of the surface and immediate surrounding of stars, stellar objects and even galactic nuclei.